2022
DOI: 10.1111/1442-1984.12365
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy and viability ofFerocactus peninsulae(Cactaceae) seeds

Abstract: Knowledge on seed dormancy is crucial for the understanding of plant population dynamics, as it controls seed germination and seed bank formation. Dormant seeds have high potential to establish in soil seed banks, but such information within Cactaceae is scarce, although it is essential for conservation programs. The aim of this study was to determine if seeds of Ferocactus peninsulae showed any kind of dormancy and to test their germination capacity after storage. This was assessed with 15 seed sowing experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
(69 reference statements)
0
4
0
1
Order By: Relevance
“…En L. diffusa no se encontró una disminución en los porcentajes de germinación en semillas de cuatro años en comparación con semillas de menor edad. El potencial para formar un banco de semillas se ha reconocido en algunas especies de cactáceas como Ferocactus townsendianus Britton & Rose, F. peninsulae y E. enneacanthus a partir de experimentos de germinación en laboratorio (Guillén-Trujillo et al, 2014;Aranda-Pineda, 2017;Rojas-Aréchiga y García-Morales, 2022).…”
Section: Discussionunclassified
“…En L. diffusa no se encontró una disminución en los porcentajes de germinación en semillas de cuatro años en comparación con semillas de menor edad. El potencial para formar un banco de semillas se ha reconocido en algunas especies de cactáceas como Ferocactus townsendianus Britton & Rose, F. peninsulae y E. enneacanthus a partir de experimentos de germinación en laboratorio (Guillén-Trujillo et al, 2014;Aranda-Pineda, 2017;Rojas-Aréchiga y García-Morales, 2022).…”
Section: Discussionunclassified
“…Seeds of different species of Cactaceae have rigid and hard coats [ 18 , 19 ]. However, recent studies increased the evidence that only physiological dormancy exists in Cactaceae seeds [ 20 , 21 ]. In Melocactus , the presence of seed dormancy was widely reported, with percentages of germinated seeds between 8 and 65%, depending on the species, genotype, harvest time, germination temperature, cultivation conditions (in vitro, Petri dish, or in vivo), and pre-treatments or treatments applied to the seeds [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority (80.9%) from 275 studied Cactaceae species are considered positive photoblastic and, any negative photoblastic was reported [ 20 , 21 ]. Flores et al [ 33 ] reported a strong influence of different Cactaceae tribes (phylogeny) on the response to light for seed germination.…”
Section: Discussionmentioning
confidence: 99%
“…After-ripening is influenced strongly by storage conditions and duration [20,22,127]. Cyclic changes in seed dormancy can occur in dry storage at constant temperatures, as was shown for rough bluegrass (Poa trivialis L.).…”
Section: The Effects Of Post-dispersal Factors On Seed Dormancy: Afte...mentioning
confidence: 96%